2004
DOI: 10.1016/j.febslet.2004.06.101
|View full text |Cite
|
Sign up to set email alerts
|

Unique natural antioxidants (NAOs) and derived purified components inhibit cell cycle progression by downregulation of ppRb and E2F in human PC3 prostate cancer cells

Abstract: Prostate cancer (PCA) is the leading cause of cancer mortality among older men in Western countries. Epidemiological studies have shown correlation between a lower risk of PCA and a higher consumption of antioxidants. However, the mechanism by which antioxidants exert their effects is still unknown. In the present study, we explored the signaling mechanism through which unique natural antioxidant derived from spinach extract (NAO) exerts their beneficial effects in the chemoprevention of PCA using human PC3 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…The fresh rhizome of Zingiber zerumbet (L.) Roscoe ex Smith (Zingiberaceae) was found to serve as source of zerumbone, which was shown to induce G2/M cell cycle arrest in human promyelocytic leukemia HL-60 cells by decreasing the cyclin B1 and CDK1 protein levels, as described elsewhere [196]. Natural antioxidant derived from spinach extract was found to exert anti-proliferative effect on human prostate cancer PC3 cells [197]. Polyphenols derived from the spinach extract were shown to increase the protein levels of CDKN1A (p21), and decrease levels of cyclin A and CDK2 proteins, as described in [197].…”
Section: Cell Cycle Regulation By Natural Compounds Affecting Cyclinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fresh rhizome of Zingiber zerumbet (L.) Roscoe ex Smith (Zingiberaceae) was found to serve as source of zerumbone, which was shown to induce G2/M cell cycle arrest in human promyelocytic leukemia HL-60 cells by decreasing the cyclin B1 and CDK1 protein levels, as described elsewhere [196]. Natural antioxidant derived from spinach extract was found to exert anti-proliferative effect on human prostate cancer PC3 cells [197]. Polyphenols derived from the spinach extract were shown to increase the protein levels of CDKN1A (p21), and decrease levels of cyclin A and CDK2 proteins, as described in [197].…”
Section: Cell Cycle Regulation By Natural Compounds Affecting Cyclinsmentioning
confidence: 99%
“…Natural antioxidant derived from spinach extract was found to exert anti-proliferative effect on human prostate cancer PC3 cells [197]. Polyphenols derived from the spinach extract were shown to increase the protein levels of CDKN1A (p21), and decrease levels of cyclin A and CDK2 proteins, as described in [197]. At the same time spinach extract polyphenols decreased the phosphorylated RB protein level, and total protein levels of retinoblastoma-like 1 (p107, also known as RBL1), and E2F1 transcription factor, as indicated in [197].…”
Section: Cell Cycle Regulation By Natural Compounds Affecting Cyclinsmentioning
confidence: 99%
“…We found that NAO induced G1 delay and cell cycle prolongation through downregulation of the protein expression of ppRb and E2F in the human PCA cell line, PC3 (Bakshi et al, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…NAO exhibits unique properties that make it an especially effective free radical scavenger (Bergman, Perelman, Dubinsky, & Grossman, 2003;Bergman et al, 2001; Ben Shaul, with strong antimutagenic potential and anti-inflammatory properties (Bakshi, Bergman, Dovrat, & Grossman, 2004;Lomnitski et al, 2003;Nyska et al, 2001Nyska et al, , 2003. Its efficiency was tested and proven in a variety of biological systems in vivo and in vitro (Breitbart et al, 2001;Lomnitski et al, 2000aLomnitski et al, , 2000bLomnitski et al, , 2003Nyska et al, 2001Nyska et al, , 2003.…”
Section: Introductionmentioning
confidence: 99%
“…β-carotene, violaxanthin, neox anthin, lutein, and phenolic acid) [29][30][31][32][33][34]. These antioxidant compounds or extracts including polyphenols, such as natural anti oxidants (NAO) [34,35] of spinach, are related to disease prevention, including cancer [31,36]. Moreover, an epidemiological study suggested that spinach is associated with reduced cancer risk [37,38].…”
Section: Discussionmentioning
confidence: 99%